High-avidity, high-IFNÎ³-producing CD8 T-cell responses following immune selection during HIV-1 infection - Keane, Niamh M.; Roberts, Stevens G.; Almedia, Coral-Ann M.; Krishnan, Tanya; Chopra, Abha; Demaine, Emma; Laird, Rebecca; Tschochner, Monika; Carlson, Jonathan M.; Mallal, Simon; Heckerman, David; James, Ian; et al. (Immunology and Cell Biology, 2012)
HIV-1 mutations, which reduce or abolish CTL responses against virus-infected cells, are frequently selected in acute and chronic HIV infection. Among population HIV-1 sequences, immune selection is evident as human leukocyte antigen (HLA) allele-associated substitutions of amino acids within or near CD8 T-cell epitopes. In these cases, the non-adapted epitope is susceptible to immune recognition until an escape mutation renders the epitope less immunogenic. However, several population-based studies have independently identified HLA-associated viral changes, which lead to the formation of a new T-cell epitope, suggesting that the immune responses that these variants or 'neo-epitopes' elicit provide an evolutionary advantage to the virus rather than the host. Here, we examined the functional characteristics of eight CD8 T-cell responses that result from viral adaptation in 125 HLA-genotyped individuals with chronic HIV-1 infection. Neo-epitopes included well-characterized immunodominant epitopes restricted by common HLA alleles, and in most cases the T-cell responses against the neo-epitope showed significantly greater functional avidity and higher IFNγ production than T cells for non-adapted epitopes, but were not more cytotoxic. Neo-epitope formation and emergence of cognate T-cell response coincident with a rise in viral load was then observed in vivo in an acutely infected individual. These findings show that HIV-1 adaptation not only abrogates the immune recognition of early targeted epitopes, but may also increase immune recognition to other epitopes, which elicit immunodominant but non-protective T-cell responses. These data have implications for immunodominance associated with polyvalent vaccines based on the diversity of chronic HIV-1 sequences.